Synthesis of eunicellane-type bicycles embedding a 1,3-cyclohexadiene moiety - Frichert, Alex; Jones, Peter G.; Lindel, Thomas (Beilstein Journal of Organic Chemistry, 2018)
The first synthesis of diterpenoid eunicellane skeletons incorporating a 1,3-cyclohexadiene moiety is presented. Key step is a low-valent titanium-induced pinacol cyclization that proved to be perfectly diastereoselective. Determination of the relative configuration of the diol was aided by the conversion to the diastereomer by oxidation and reduction. Conformational analysis of some of the resulting diols obtained under McMurry conditions was complicated by the presence of several conformers of similar energy. The pinacol coupling appears to start at the ketone, as indicated by the selective reduction of non-cyclizing cyclohexane systems that were synthesized from limonene oxide. The title compounds and their synthetic precursors are prone to aromatization on contact with air oxygen. Attempted synthesis of cyclohexene-containing eunicellane bicycles by elimination of water from tertiary alkynyl carbinols afforded novel allene systems. Our study may be of help towards the total synthesis of solenopodin or klysimplexin derivatives.
Keywords: conformational analysis; low valent titanium; marine natural products; pinacol coupling; ten-membered rings

(untitled) - Bloor, S. J.; Schmitz, F. J.; Hossain, M. B.; Van der Helm, D. (J. Org. Chem., 1992)

(untitled) - Ortega, M. J.; Zubía, E.; Salvá, J. (J. Nat. Prod., 1997)

(untitled) - Chen, B.-W.; Chao, C.-H.; Su, J.-H.; Tsai, C.-W.; Wang, W.-H.; Wen, Z.-H.; Huang, C.-Y.; Sung, P.-J.; Wu, Y.-C.; Sheu, J.-H. (Org. Biomol. Chem., 2011)

(untitled) - Chen, Y.-H.; Tai, C.-Y.; Su, Y.-D.; Chang, Y.-C.; Lu, M.-C.; Weng, C.-F.; Su, J.-H.; Hwang, T.-L.; Wu, Y.-C.; Sung, P.-J. (Mar. Drugs, 2011)

(untitled) - Angulo-Preckler, C.; Genta-Jouve, G.; Mahajan, N.; de la Cruz, M.; de Pedro, N.; Reyes, F.; Iken, K.; Avila, C.; Thomas, O. P. (J. Nat. Prod., 2016)

(untitled) - Pinto, A. C.; Pizzolatti, M. G.; de A. Epifanio, R.; Frankmölle, W.; Fenical, W. (Tetrahedron, 1997)

(untitled) - Rinkel, J.; Rabe, P.; Chen, X.; Köllner, T. G.; Chen, F.; Dickschat, J. S. (Chem. – Eur. J., 2017)

(untitled) - Nicolaou, K. C.; Ohshima, T.; Hosokawa, S.; van Delft, F. L.; Vourloumis, D.; Xu, J. Y.; Pfefferkorn, J.; Kim, S. (J. Am. Chem. Soc., 1998)

(untitled) - Castoldi, D.; Caggiano, L.; Panigada, L.; Sharon, O.; Costa, A. M.; Gennari, C. (Angew. Chem., 2005)
Angew. Chem., Int. Ed. 2005, 44, 588–591. doi:10.1002/anie.200461767

(untitled) - Nii, K.; Tagami, K.; Matsuoka, K.; Munakata, T.; Ooi, T.; Kusumi, T. (Org. Lett., 2006)

(untitled) - Al Batal, M.; Jones, P. G.; Lindel, T. (Eur. J. Org. Chem., 2013)

(untitled) - Kato, N.; Kataoka, H.; Ohbuchi, S.; Tanaka, S.; Takeshita, H. (J. Chem. Soc., Chem. Commun., 1988)

(untitled) - Swindell, C. S.; Fan, W. (J. Org. Chem., 1996)

(untitled) - Yamato, T.; Fujita, K.; Okuyama, K.-i.; Tsuzuki, H. (New J. Chem., 2000)

(untitled) - Sergeeva, E. V.; Rozenberg, V. I.; Antonov, D. Y.; Vorontsov, E. V.; Starikova, Z. A.; Fedyanin, I. V.; Hopf, H. (Chem. – Eur. J., 2005)

(untitled) - Saisyo, T.; Shiino, M.; Shimizu, T.; Paudel, A.; Yamato, T. (J. Chem. Res., 2008)

(untitled) - Castagnolo, D.; Contemori, L.; Maccari, G.; Avramova, S. I.; Neri, A.; Sgaragli, G.; Botta, M. (ACS Med. Chem. Lett., 2010)

(untitled) - Nicolaou, K. C.; Yang, Z.; Liu, J.-J.; Nantermet, P. G.; Claiborne, C. F.; Renaud, J.; Guy, R. K.; Shibayama, K. (J. Am. Chem. Soc., 1995)

(untitled) - Ferri, F.; Brückner, R.; Herges, R. (New J. Chem., 1998)

(untitled) - Williams, D. R.; Heidebrecht, R. W. (J. Am. Chem. Soc., 2003)

(untitled) - Nicolaou, K. C.; Sorensen, E. J.; Discordia, R.; Hwang, C.-K.; Minto, R. E.; Bharucha, K. N.; Bergman, R. G. (Angew. Chem., 1992)

(untitled) - Comanita, B. M.; Heuft, M. A.; Rietveld, T.; Fallis, A. G. (Isr. J. Chem., 2000)

(untitled) - McMurry, J. E.; Miller, D. D. (J. Am. Chem. Soc., 1983)

(untitled) - Blair, M.; Andrews, P. C.; Fraser, B. H.; Forsyth, C. M.; Junk, P. C.; Massi, M.; Tuck, K. L. (Synthesis, 2007)

(untitled) - Masters, K.-S.; Flynn, B. L. (J. Org. Chem., 2008)

(untitled) - Corey, E. J.; Tian, Y. (Org. Lett., 2005)

(untitled) - Ambrose, M. G.; Binkley, R. W. (J. Org. Chem., 1983)

(untitled) - Netscher, T.; Bohrer, P. (Tetrahedron Lett., 1996)

(untitled) - Hendrickson, J. B.; Giga, A.; Wareing, J. (J. Am. Chem. Soc., 1974)

(untitled) - Braverman, S.; Pechenick, T.; Zafrani, Y. (Tetrahedron Lett., 2001)